2021
DOI: 10.48550/arxiv.2101.08750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Gospel According to Q: Understanding the QAnon Conspiracy from the Perspective of Canonical Information

Abstract: The QAnon conspiracy theory claims that a cabal of (literally) blood thirsty politicians and media personalities are engaged in a war to destroy society. By interpreting cryptic "drops" of information from an anonymous insider calling themselves Q, adherents of the conspiracy theory believe that they are being led by Donald Trump in an active fight against this cabal. QAnon has been covered extensively by the media, as its adherents have been involved in multiple violent acts, including the January 6th, 2021 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…We use Google's Perspective API [1] to measure the toxicity of the discussion surrounding the conspiracy theories. We use the Severe Toxicity model to characterize this aspect since previous work found it more reliable and less prone to "false positives" when measuring toxic speech [3,13,30].…”
Section: General Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…We use Google's Perspective API [1] to measure the toxicity of the discussion surrounding the conspiracy theories. We use the Severe Toxicity model to characterize this aspect since previous work found it more reliable and less prone to "false positives" when measuring toxic speech [3,13,30].…”
Section: General Characterizationmentioning
confidence: 99%
“…Our qualitative analysis finds that /r/news, /r/politics, and /r/worldnews merely report on the conspiracy theories without delving into the details. Looking at Twitter, we find that the platform users are mostly critical of the conspiracies and the 3 A person who sent pipe bombs to Democratic officials in 2020. actors spreading them. Conversely, more politically polarized communities (e.g., /r/The_Donald) primarily discuss the conspiracy to defend the actors involved in it.…”
Section: Influence Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, previous studies explored the topics and dissemination of Q's messages on various online platforms and found that QAnon borrows theories from other conspiracies such as Pizzagate [60], shares moral values with Christian theology [53] and QAnon followers are likely to use violent rhetoric on Twitter [65]. While the existing studies provide valuable characterization of the QAnon movement across platforms [1], deeper psychological and sociological exploration is required to deter increased engagement with QAnon [35]. Our work fills this gap by first establishing QAnon social imaginaries symbolizing collective interpretation of reality by QAnon and then using those imaginaries to identify expressions of dissonance in the QAnon community.…”
Section: What Is Qanon?: Origin and Community Dynamicsmentioning
confidence: 99%
“…We use qalerts.app, a website that aggregates Q-drops from image boards. While the exact agency of qalerts.app is unknown, it is a common resource used by QAnon communities 1 and also by other researchers studying QAnon [1]. There are several other Q-drop aggregation sites across internet however, most of the sites contain nearly similar record of Q posts (see Table 1 in Aliapoulios et al [1]).…”
Section: Datamentioning
confidence: 99%